Egypt Wheat Trader Survey, 1996 - International Food Policy Research Institute (International Food Policy Research Institute, 2000)
The questionnaire was administered to 1,984 geographically weighted, randomly selected wheat and wheat flour traders located in 141 districts in 18 governorates from August through December, 1996. Topics include the general characteristics of the traders; the structure of their trading business; their trading flows and networks; their transport, communication, storage and cost structures; credit transactions; relative profitability and investment activities; and their opinions on the role of government in regulating trading activities.